Nanometer friction paper-based positive electrode material with interpenetrating network structure and preparation method of nanometer friction paper-based positive electrode material

By forming a nano-friction paper-based positive electrode material with an interpenetrating network structure in the paper-based material, the problem that paper-based material is difficult to uniformly generate friction charges in flexible electronic devices is solved, efficient charge transfer and signal stability are achieved, and the performance of flexible electronic devices is improved.

CN119800772AActive Publication Date: 2025-04-11SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411972877.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing paper-based materials are difficult to produce friction charge uniformly in flexible electronic devices, and the sensing positive electrode materials have weak charge transfer capabilities, which limits their application in the field of flexible electronic devices.

Method used

A nano-friction paper-based positive electrode material with an interpenetrating network structure is used, and the preparation method includes forming an interpenetrating network structure by releasing and impregnation treatment, and combining carboxymethyl cellulose as a friction surface constructor.

Benefits of technology

It realizes uniformly generating friction charge and effective current transmission in paper-based materials, improves the stability and measurement accuracy of nano friction signals, and overcomes the problem of signal distortion caused by external interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800772A_ABST
    Figure CN119800772A_ABST
Patent Text Reader

Abstract

The invention relates to the cross technical field of preparation of special papermaking, carbon fiber-based materials and sensing materials, in particular to a nano friction paper-based positive electrode material with an interpenetrating network structure and a preparation method of the nano friction paper-based positive electrode material. The paper-based positive electrode material is prepared by taking aramid fibrid as a basic framework, taking aramid pulp as a forming auxiliary material and carrying out treatment surface enhancement and triboelectrification enhancement by adopting a carboxymethyl cellulose dispersion liquid. The process effectively solves the problem that the nano friction signal is weak and is easy to distort due to interference of external electromagnetism, vibration and the like, and improves the measurement accuracy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the cross-technical field of special papermaking, carbon fiber-based materials and sensor material preparation, and in particular to a nano friction paper-based positive electrode material with an interpenetrating network structure and a preparation method thereof. Background Art

[0002] In the context of the continuous development and integration of modern materials science and electronic technology, the field of flexible electronic devices has attracted much attention. Paper-based materials have become potential preferred materials for flexible electronic device substrates because of their low cost, wide sources, biodegradability and natural flexibility. In the working principles of many flexible electronic devices, triboelectric charging and charge transfer processes are crucial. For example, in devices such as triboelectric nanogenerators, materials must be able to evenly generate triboelectric charges and construct effective current transmission paths to achieve efficient power conversion and transmission. However, the inherent characteristics of paper-based materials lead to obvious deficiencies in these two aspects. Its surface microstructure is complex and uneven, and the distribution of chemical components lacks regularity, making it difficult to evenly generate triboelectric charges on the entire material surface during friction. The sensing positive electrode material has a weak ability to transfer the generated charges, which greatly limits the further expansion and performance improvement of triboelectric-related applications of paper-based materials in the field of flexible electronic devices.

[0003] Paper-based friction nanogenerators have been developing continuously in recent years. CN113644841A has made a folded paper-based friction nanogenerator with a double-helix multilayer structure. CN118610691B disperses, stirs, and electrospins meta-aramid electrospinning solution and polyvinylidene fluoride electrospinning solution to obtain meta-aramid-polyvinylidene fluoride composite nanofiber lithium battery diaphragm, realizing the diaphragm's adaptive adjustment of the voltage and flow rate of the electrospinning device. CN114938156 A uses ethyl acrylate, a crosslinking agent, an initiator, and a solvent to make an ion gel as an electrode layer, a threaded silicone tube as a negative friction layer, and a non-woven aramid cloth as a positive friction layer, and assembles them into a tubular structure, wherein the non-woven aramid cloth is spirally wound on the surface of the ion gel electrode, and the threaded silicone tube negative friction layer is wrapped on the surface of the non-woven aramid cloth to obtain a friction nanogenerator. However, at present, the sensing positive electrode material has a weak ability to transfer the generated charge, which limits the development of the domestic nano friction power generation and nano friction sensing fields. Summary of the invention

[0004] In view of the problem in the prior art that it is difficult to evenly generate friction charges and the effective current transmission path is insufficient when using paper-based materials as sensing positive electrode materials, the present invention provides a nano-friction paper-based positive electrode material with an interpenetrating network structure and a preparation method thereof.

[0005] The present invention is achieved through the following technical solutions: A method for preparing a nano-friction paper-based positive electrode material with an interpenetrating network structure comprises the following steps: Step 1: placing aramid fiber precipitation in deionized water, and obtaining aramid fiber precipitation slurry A through soaking and decomposition treatment; Aramid pulp with large specific surface area, rich terminal groups and strong interweaving is obtained by rolling, beating and refining the waste aramid fibers to obtain aramid pulp B after debonding and dispersion. Step 2: adding carbon fiber to aramid precipitation slurry A and aramid pulp slurry B in a certain proportion, and performing deflaking treatment to obtain mixed slurry C; Step 3: The mixed slurry C is rapidly dehydrated, cold pressed, and vacuum dried to prepare a carbon fiber composite paper D; Step 4: impregnating the carbon fiber composite paper D in a carboxymethyl cellulose aqueous dispersion to obtain an optimized carbon fiber composite paper E; Step 5: vacuum-dry and hot-press the optimized carbon fiber composite paper E to obtain a paper-based positive electrode material F.

[0006] Preferably, in step 1, in the preparation of aramid precipitation slurry A, the aramid precipitation fibers are para-aramid fibers with a diameter of 5 to 10 μm; During soaking, the concentration of deionized water is 0.8-1.1 g / L, the time is 6-9 hours, and the indoor ambient temperature is 20-25°C; During degassing, the speed is 20000~25000 rpm.

[0007] Preferably, in step 1, when preparing aramid pulp slurry B, the waste aramid fibers are derived from aramid protective clothing and woven scraps in the production process; When rolling, the feed rate is 40-50kg / h; During pulping, the waste aramid fiber is treated with a pulping concentration of 3% to 6% and the time is 3 to 5 hours; During refining, the refining pressure is 700~800pa, the time is 0.5~1.0h, and the specific surface area of ​​aramid pulp is 10~12m 2 / g; The time for deflaking is 0.5 to 1.0 h, and the concentration of the aramid pulp slurry B after deflaking is 3% to 5% g / L.

[0008] Preferably, in step 2, the carbon fiber is asphalt-based carbon fiber with a length of 5 to 6 mm, a diameter of 7 to 8 μm, and an electrical conductivity of 10² to 10 4 S / cm.

[0009] Preferably, the absolute dry ratio of aramid precipitate, carbon fiber and aramid pulp is (1.1-0.8) g: (0.21-0.22) g: (1.1-0.8) g, and the slurry concentration after the three are mixed is 2.17-2.23 g / L; During degassing, the speed is 25000-30000 rpm.

[0010] Preferably, in step 3, the homogenization is performed 10 to 15 times before rapid dehydration, and the dehydration time is 1.0 to 2.0 seconds; During cold pressing, absorbent felt is placed on the upper and lower sides of the dehydrated sample. The cold pressing pressure is 20-40MPa and the time is 8-10min. During vacuum drying, the temperature is 90-100°C; the vacuum degree is 99.5-99.9 kPa; and the time is 8-10 minutes.

[0011] Preferably, in step 4, during the impregnation, the average molecular weight of the carboxymethyl cellulose is 6000 to 17000, the mass fraction of the carboxymethyl cellulose solution is 0.8 wt% to 1.0 wt%, and the impregnation time is 1 to 2 min.

[0012] Preferably, in step 5, during vacuum drying, the temperature is 90-100° C., the vacuum degree is 99.5-99.9 kPa, and the time is 8-10 min; During hot pressing finishing, the temperature is 180-200°C, the time is 10-20 minutes, and the pressure is 13-15 MPa.

[0013] A paper-based positive electrode material obtained according to the method for preparing a nano-friction paper-based positive electrode material with an interpenetrating network structure.

[0014] A nano friction generator comprises a positive electrode made of the positive electrode material and a negative electrode made of a polytetrafluoroethylene film.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The method for preparing a nano-friction paper-based positive electrode material with an interpenetrating network structure of the present invention uses an interpenetrating network of carbon fiber, aramid precipitated fiber, and aramid pulp as a skeleton, and carboxymethyl cellulose as a friction surface builder to prepare a paper-based positive electrode material, thereby overcoming the problem that the nano-friction signal is weak and susceptible to interference, and external electromagnetic, vibration and other interferences may cause signal distortion, affecting the measurement accuracy and cannot be solved. On the one hand, aramid pulp fibers are introduced to improve the uniformity of paper and promote the interweaving of fiber networks. On the other hand, low-concentration carboxymethyl cellulose is used for impregnation and bonding to prevent the closure of the pore structure. In this structure, the molecular structure of the introduced aramid pulp is composed of alternating benzene rings and amide bonds, and the molecular structure has a high carbon content. Its high carbon content is conducive to the formation of a paper base with higher conductivity after carbonization treatment; at the same time, the dispersibility of the mixed pulp also helps to improve the uniformity of the base paper.

[0016] Aramid pulp not only has good flexibility and adhesion, but also can enhance the flexibility and strength of paper during the papermaking process, making up for the brittleness and interface inertness defects of carbon fiber. During the carbonization process, it forms a rich conductive network, thereby optimizing the conductive properties of paper and achieving a balance between strength, toughness and conductivity. In addition, the proportion of aramid pulp is obtained through long-term process optimization. Too high aramid pulp content is not conducive to carboxymethyl cellulose impregnation, and too high or too low proportions are not conducive to improving paper performance.

[0017] On the basis of introducing aramid pulp as an auxiliary, the adhesion and reinforcement of the interweaving points between carbon fiber and carbon fiber, carbon fiber and aramid pulp, and aramid pulp are strengthened through the impregnation of ultra-low concentration carboxymethyl cellulose; the concentration of carboxymethyl cellulose is the result of process optimization. At ultra-low concentration, it not only supplements the insufficient contact of fibers, but also facilitates the construction of conductive network after carbonization, and ensures the strength and stress transfer during stretching. It not only supplements the insufficient contact of fibers, but also facilitates the construction of conductive network after carbonization, and ensures the strength and stress transfer during stretching.

[0018] The preferred aramid pulp terminal groups contain rich amino groups and have good compatibility and self-binding ability with carboxymethyl cellulose, ensuring high performance at low concentrations. The principle is that the aramid pulp terminal groups can form extensive hydrogen bonds with carboxymethyl cellulose, and the solidification of carboxymethyl cellulose can cross-link the pulp fiber filaments, achieving high-strength bonding through the combined action of chemistry and physics. This technical point has not been reported in other disclosed technologies of the present invention.

[0019] Furthermore, the pulp decomposition speed, fiber addition order, drying temperature, hot pressing finishing temperature and pressure are all the results of long-term process optimization. The optimization of these parameters helps to improve paper quality and save energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a flow chart of a method for preparing a nano-friction paper-based positive electrode material having an interpenetrating network structure according to the present invention; Figure 2 This is a voltage diagram obtained by the sensing application of the carbon fiber paper-based positive electrode material obtained in Example 1; Figure 3 This is the current diagram obtained by the sensing application of the carbon fiber paper-based positive electrode material obtained in Example 1; Figure 4 This is the charge diagram obtained by the sensing application of the carbon fiber paper-based cathode material obtained in Example 1; Figure 5 is a SEM image of the surface of the carbon fiber paper-based positive electrode material obtained in Example 1; Figure 6This is the XRD performance test of carbon fiber paper-based positive electrode material in implementation case 1. DETAILED DESCRIPTION

[0021] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0022] The present invention discloses a method for preparing a nano friction paper-based positive electrode material having an interpenetrating network structure, referring to Figure 1 , including the following steps: Step 1, placing the aramid fiber precipitate A in deionized water with a concentration of 0.8-1.1 g / L, soaking it at an indoor ambient temperature of 20-25° C. for 6-9 hours, and then dispersing it at a rotation speed of 20000-25000 rpm to obtain a uniformly dispersed aramid fiber precipitate slurry A.

[0023] Waste aramid fibers (derived from aramid protective clothing and woven scraps in the production process) are subjected to thread rolling, beating and grinding to obtain aramid pulp with high specific surface area, high terminal bifurcation and high interweaving force, and aramid pulp slurry B is obtained after debonding and dispersion.

[0024] Among them, thread rolling is carried out by a thread rolling machine, the model of the thread rolling machine is TMF250, and the feeding time of the thread rolling machine is 40-50kg / h; the pulping adopts a KDH100-XT beater, the meta-aramid fiber treatment pulping concentration is 3%-6%, and the time is 3-5h; the refining adopts a FZ-102 refiner, the refining treatment pressure in the refiner is 700-800pa, the time is 0.5-1.0h, the specific surface area of ​​the obtained aramid pulp is 10-12 m2 / g, the decomposition concentration is 3%-5% g / L, and the decomposition time is 0.5-1.0h.

[0025] Step 2: According to the absolute dry ratio of aramid precipitate, carbon fiber and aramid pulp of (1.1-0.8) g: (0.21-0.22) g: (1.1-0.8) g, the three are mixed and dispersed at a speed of 25000-30000 rpm to obtain a mixed slurry C with a concentration of 2.17-2.23 g / L.

[0026] Step 3: The mixed slurry C is rapidly dehydrated, cold pressed and vacuum dried to prepare carbon fiber composite paper D.

[0027] Among them, the carbon fiber is asphalt-based carbon fiber with a length of 5 to 6 mm, a diameter of 7 to 8 μm., and an electrical conductivity of 10² to 10 4S / cm; homogenization is required 10-15 times before rapid dehydration, and the dehydration time is 1.0-2.0s; during cold pressing, the dehydrated sample is padded with wool absorbent felt, and the cold pressing pressure is 20-40MPa; the time is 8-10min. During vacuum drying, the temperature is 90-100℃; the vacuum degree is 99.5-99.9kPa; the time is 8-10min.

[0028] Step 4: Immersing the carbon fiber composite paper D in a carboxymethyl cellulose dispersion having a mass fraction of 0.8 wt% to 1.0 wt% of carboxymethyl cellulose for 1 to 2 minutes, wherein the average molecular weight of the carboxymethyl cellulose is 6000 to 17000; Step 5, drying and hot pressing are performed to obtain the carbon nanofiber paper-based positive electrode material. The vacuum drying temperature is 90-100°C, the vacuum degree is 99.5-99.9 kPa, the time is 8-10 minutes, the hot pressing finishing temperature is 180-200°C, the time is 10-20 minutes, and the pressure is 13-15 MPa.

[0029] The invention discloses a method for preparing a nano-friction paper-based positive electrode material with an interpenetrating network structure. The method uses aramid fiber precipitation as a basic skeleton, aramid pulp as a molding auxiliary material, and a carboxymethyl cellulose dispersion liquid for surface enhancement and friction electrification strengthening, thereby preparing a paper-based positive electrode material. The process effectively solves the problem that the nano-friction signal is weak and easily distorted due to external electromagnetic, vibration and other interferences, and improves the measurement accuracy.

[0030] The deflaker, paper sheet former, dryer, hot press, etc. used in the preparation method proposed in the present invention are all conventional equipment, and the process is environmentally friendly, which lays a good foundation for industrialization and scale-up and has a high market competitive advantage.

[0031] The invention also discloses a paper-based positive electrode material obtained according to the method for preparing a nano-friction paper-based positive electrode material with an interpenetrating network structure.

[0032] The present invention also discloses a nano friction generator, comprising a positive electrode made of the above-mentioned positive electrode material and a negative electrode made of a polytetrafluoroethylene film. Specifically, the preparation of the nano friction generator is as follows: a copper foil tape with a thickness of 18μm to 25μm is pasted on the positive electrode made of a carbon fiber paper-based positive electrode material F, and a wire is attached, and it is rubbed and collided with a negative electrode made of a polytetrafluoroethylene film G with a thickness of 0.1 to 0.5mm and attached with the wire and the same copper foil tape for sensing application.

[0033] Example 1 Step 1: A aramid fiber with a dry weight of 0.88 g is placed in deionized water, and after 8 hours of soaking treatment, a uniformly dispersed aramid fiber slurry A is obtained. A aramid pulp with a large specific surface area, rich ends and strong interweaving is obtained by spinning, beating and refining the waste aramid fibers, and an aramid pulp slurry B is obtained after decomposition and dispersion, wherein the ratio of aramid pulp B to water is 1.1 g2: 2L, and its dry weight is 1.1 g.

[0034] Step 2: Add 0.21 g of carbon fiber and aramid pulp dispersed slurry to aramid precipitated fiber slurry, and perform decomposition treatment to form mixed slurry C, and the decomposition speed is 25000 rpm; prepare carbon fiber composite paper D by dehydration, cold pressing for 8 minutes, and vacuum drying steps, with a drying vacuum degree of 99.5 kPa, a temperature of 105 ° C, a time of 8 minutes, a dried paper weight of 2.26 g, and a paper sheet thickness of 0.077 mm.

[0035] Step 3: The carbon fiber composite paper D is immersed in a carboxymethyl cellulose aqueous dispersion with a mass fraction of 0.8 wt%, and then dried and hot-pressed. During drying, the temperature is 60°C and the time is 12 min; during hot-pressing finishing, the temperature is 200°C, the time is 15 min, and the pressure is 13 MPa. Finally, a nano-carbon fiber paper-based positive electrode material is obtained.

[0036] Step 4: Paste a copper foil tape with a thickness of 18 μm on the carbon fiber paper-based positive electrode material E and attach a wire, and rub and collide it with a polytetrafluoroethylene film F with a thickness of 0.1 mm attached to the wire and the same copper foil tape for sensing application.

[0037] The carbon fiber paper-based positive electrode material based on the friction electrification principle obtained in Example 1 has a paper basis weight of 70 g / m2, a thickness of 0.077 mm, and a paper weight of 2.26 g. Figure 5 It can be clearly seen that the material has a mutual transmission grid structure. The carboxymethyl cellulose is mainly distributed on the surface of the aramid fibrils. The bond between the carbon fiber and the aramid fibrils with a filamentous structure is relatively strong. The reason is that the surface of the aramid fibrils is rich in many active groups. These groups enable the carbon fiber to be evenly dispersed and tightly entangled by the aramid fibrils through physical interweaving, thereby effectively curbing the agglomeration of the carbon fiber and promoting its uniform dispersion in the composite system. Figure 6 , the stretching vibration of carbon fiber can be observed at 26.57 degrees, which also proves that the prepared carbon fiber paper-based positive electrode material meets the requirements. In the sensing application, the current can reach 74.58nA at a frequency of 5HZ, the voltage can reach 10.50V, and the generated charge can reach 1.39nC, which has efficient sensing function.

[0038] Table 1 Sensing parameters of the carbon fiber paper-based positive electrode material based on the friction electrification principle prepared in Example 1 at friction rates of 3 Hz, 5 Hz, and 7 Hz

[0039] Example 2 Step 1: A aramid fiber with a dry weight of 1.09 g was placed in deionized water, and after 8 hours of soaking treatment, a uniformly dispersed aramid fiber slurry A was obtained. A aramid pulp with a large specific surface area, rich ends and strong interweaving was obtained by spinning, beating and refining the waste aramid fibers, and an aramid pulp slurry B was obtained after decomposition and dispersion, wherein the ratio of aramid pulp B to water was 0.87 g: 2L, and its dry weight was 0.87 g.

[0040] Step 2: Add 0.22 g of carbon fiber and aramid pulp slurry to aramid precipitated fiber slurry, and perform decomposition treatment to form mixed slurry C, and the decomposition speed is 30000 rpm; prepare carbon fiber composite paper D through dehydration, cold pressing for 8 minutes, and vacuum drying steps. During drying, the drying vacuum degree is 99.9 kPa, the temperature is 105 ° C, the time is 10 min, the dried paper weight is 2.25 g, and the paper sheet thickness is 0.104 mm.

[0041] Step 3: The carbon fiber composite paper D is impregnated in a carboxymethyl cellulose dispersion with a carboxymethyl cellulose mass fraction of 0.9wt%, and then dried and hot-pressed. During drying, the temperature is 70°C and the time is 12min; during hot-pressing finishing, the temperature is 200°C, the time is 14min, and the pressure is 13MPa. Finally, a nano-carbon fiber paper-based positive electrode material is obtained.

[0042] Step 4: A copper foil tape with a thickness of 25 μm is pasted on the carbon fiber paper-based positive electrode material E and a wire is attached, and it is rubbed and collided with a 0.5 mm thick polytetrafluoroethylene film F with attached wires and the same copper foil tape for sensing application.

[0043] The carbon fiber paper-based positive electrode material based on the friction electrification principle obtained in Example 2 has a paper basis weight of 70 g / m 2 , thickness is 0.104 mm, paper weight is 2.25g, in sensing applications, the current can reach 77.15nA at a frequency of 5HZ, the voltage can reach 10.79V, and the charge generated can reach 1.58nC, which has efficient sensing function.

[0044] Example 3 Step 1: A aramid fiber with a dry weight of 0.90 g was placed in deionized water, and after 8 hours of soaking treatment, a uniformly dispersed aramid fiber slurry A was obtained. A aramid pulp with a large specific surface area, rich ends and strong interweaving was obtained by spinning, beating and refining the waste aramid fibers, and an aramid pulp slurry B was obtained after decomposition and dispersion, wherein the ratio of aramid pulp B to water was 1.09 g: 2L, and its dry weight was 1.09 g.

[0045] Step 2: Add 0.21 g of carbon fiber and aramid pulp slurry to aramid precipitated fiber slurry, and perform decomposition treatment to form mixed slurry C, and the decomposition speed is 25000 rpm; prepare carbon fiber composite paper D through dehydration, cold pressing for 8 minutes, and vacuum drying steps. During drying, the drying vacuum degree is 99.6 kPa, the temperature is 105°C, the time is 8 minutes, the dried paper weight is 2.17 g, and the paper sheet thickness is 0.097 mm.

[0046] Step 3: The carbon fiber composite paper D is impregnated in a carboxymethyl cellulose aqueous dispersion with a carboxymethyl cellulose mass fraction of 0.8 wt%, and then dried and hot-pressed. During drying, the temperature is 60°C and the time is 10 min; during hot-pressing finishing, the temperature is 200°C, the time is 15 min, and the pressure is 13 MPa. Finally, a nano-carbon fiber paper-based positive electrode material is obtained.

[0047] Step 4: Paste a copper foil tape with a thickness of 20 μm on the carbon fiber paper-based positive electrode material E and attach a wire, and rub and collide it with a polytetrafluoroethylene film F with a thickness of 0.3 mm attached to the wire and the same copper foil tape for sensing application.

[0048] The carbon fiber paper-based positive electrode material based on the friction electrification principle obtained in Example 3 has a paper basis weight of 70 g / m 2 , thickness is 0.097 mm, paper weight is 2.17g, in sensing applications, the current can reach 76.52nA at a frequency of 5HZ, the voltage can reach 11.62V, and the charge generated can reach 1.47nC, which has efficient sensing function.

[0049] Example 4 Step 1: A aramid fiber with a dry weight of 1.09 g was placed in deionized water, and after 8 hours of soaking treatment, a uniformly dispersed aramid fiber slurry A was obtained. A aramid pulp with a large specific surface area, rich ends and strong interweaving was obtained by spinning, beating and refining the waste aramid fibers, and an aramid pulp slurry B was obtained after decomposition and dispersion, wherein the ratio of aramid pulp B to water was 0.87 g: 2L, and its dry weight was 0.87 g.

[0050] Step 2: Add 0.21 g of carbon fiber and aramid pulp slurry to aramid precipitated fiber slurry, and perform decomposition treatment to form mixed slurry C, and the decomposition speed is 25000 rpm; prepare carbon fiber composite paper D through dehydration, cold pressing for 8 minutes, and vacuum drying steps. During drying, the drying vacuum degree is 99.7 kPa, the temperature is 105°C, the time is 8 minutes, the dried paper weight is 2.23 g, and the paper sheet thickness is 0.103 mm.

[0051] Step 3: The carbon fiber composite paper D is impregnated in a carboxymethyl cellulose aqueous dispersion with a carboxymethyl cellulose mass fraction of 0.9 wt%, and then dried and hot-pressed. During drying, the temperature is 75°C and the time is 12 min; during hot-pressing finishing, the temperature is 200°C, the time is 15 min, and the pressure is 13 MPa. Finally, a nano-carbon fiber paper-based positive electrode material is obtained.

[0052] Step 4: Paste a copper foil tape with a thickness of 23 μm on the carbon fiber paper-based positive electrode material E and attach a wire, and rub and collide it with a polytetrafluoroethylene film F with a thickness of 0.3 mm attached to the wire and the same copper foil tape for sensing application.

[0053] The carbon fiber paper-based positive electrode material based on the friction electrification principle obtained in Example 4 has a paper basis weight of 70 g / m 2 , thickness is 0.103mm, paper weight is 2.23g, in sensing applications, the current can reach 72.48nA at a frequency of 5HZ, the voltage can reach 10.28V, and the charge generated can reach 1.24nC, which has efficient sensing function.

[0054] Example 5 Step 1: A aramid fiber with a dry weight of 0.88 g was placed in deionized water, and after 8 hours of soaking treatment, a uniformly dispersed aramid fiber slurry A was obtained. A aramid pulp with a large specific surface area, rich ends and strong interweaving was obtained by spinning, beating and refining the waste aramid fibers, and an aramid pulp slurry B was obtained after decomposition and dispersion, wherein the ratio of aramid pulp B to water was 1.1 g: 2L, and its dry weight was 1.1 g.

[0055] Step 2: Add 0.21 g of carbon fiber and aramid pulp slurry to aramid fiber precipitate slurry, and perform decomposition treatment to form mixed slurry C, and the decomposition speed is 25000 rpm; prepare carbon fiber composite paper D through dehydration, cold pressing for 8 minutes, and drying steps. During drying, the temperature is 100°C, the time is 10 minutes, the dried paper weight is 2.18 g, and the paper sheet thickness is 0.086 mm.

[0056] Step 3: The carbon fiber composite paper D is immersed in a carboxymethyl cellulose aqueous dispersion with a carboxymethyl cellulose mass fraction of 0.9 wt%, and then vacuum dried and hot pressed. During drying, the vacuum degree is 99.8 kPa, the temperature is 70 ° C, and the time is 12 min; during hot pressing finishing, the temperature is 200 ° C, the time is 15 min, and the pressure is 13 MPa. Finally, a nano-carbon fiber paper-based positive electrode material is obtained. Step 4: A copper foil tape with a thickness of 21 μm is pasted on the carbon fiber paper-based positive electrode material E and a wire is attached, and it is rubbed and collided with a polytetrafluoroethylene film F with a thickness of 0.2 mm attached with the wire and the same copper foil tape for sensing application.

[0057] The carbon fiber paper-based positive electrode material based on the friction electrification principle obtained in Example 5 has a paper basis weight of 70 g / m 2 , thickness is 0.086mm, paper weight is 2.18g, in sensing applications, the current can reach 75.32nA at a frequency of 5HZ, the voltage can reach 11.25V, and the charge generated can reach 1.43nC, which has efficient sensing function.

[0058] Table 2 Technical parameters of carbon fiber paper-based positive electrode materials based on the triboelectric principle prepared in Examples 1 to 5

[0059] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A method for preparing a nano-friction paper-based positive electrode material having an interpenetrating network structure, characterized in that: The following steps are involved: Step 1: placing aramid fiber precipitation in deionized water, and obtaining aramid fiber precipitation slurry A through soaking and decomposition treatment; Aramid pulp with large specific surface area, rich terminal groups and strong interweaving is obtained by rolling, beating and refining the waste aramid fibers to obtain aramid pulp B after debonding and dispersion. Step 2: adding carbon fiber to aramid precipitation slurry A and aramid pulp slurry B in a certain proportion, and performing deflaking treatment to obtain mixed slurry C; Step 3: The mixed slurry C is rapidly dehydrated, cold pressed, and vacuum dried to prepare a carbon fiber composite paper D; Step 4: impregnating the carbon fiber composite paper D in a carboxymethyl cellulose aqueous dispersion to obtain an optimized carbon fiber composite paper E; Step 5: vacuum-dry and hot-press the optimized carbon fiber composite paper E to obtain a paper-based positive electrode material F.

2. The method for preparing a nano-friction paper-based positive electrode material having an interpenetrating network structure according to claim 1, characterized in that: In step 1, in the preparation of aramid precipitation slurry A, the aramid precipitation fibers are para-aramid fibers with a diameter of 5 to 10 μm; During soaking, the concentration of deionized water is 0.8-1.1 g / L, the time is 6-9 hours, and the indoor ambient temperature is 20-25°C; During degassing, the speed is 20000~25000 rpm.

3. The method for preparing a nano-friction paper-based positive electrode material having an interpenetrating network structure according to claim 1, characterized in that: In step 1, when preparing aramid pulp slurry B, the waste aramid fibers are derived from aramid protective clothing and woven scraps in the production process; When rolling, the feed rate is 40-50kg / h; During pulping, the waste aramid fiber is treated with a pulping concentration of 3% to 6% and the time is 3 to 5 hours; During refining, the refining pressure is 700~800pa and the time is 0.5~1.0h; The specific surface area of ​​the aramid pulp finally obtained is 10-12 m 2 / g, the concentration of aramid pulp slurry B after deflaking is 3%~5% g / L, and the deflaking time is 0.5~1.0h.

4. The method for preparing a nano-friction paper-based positive electrode material having an interpenetrating network structure according to claim 1, characterized in that: In step 2, the carbon fiber is a pitch-based carbon fiber with a length of 5 to 6 mm, a diameter of 7 to 8 μm, and an electrical conductivity of 10² to 10 4 S / cm.

5. The method for preparing a nano-friction paper-based positive electrode material having an interpenetrating network structure according to claim 1, characterized in that: The absolute dry ratio of aramid precipitate, carbon fiber and aramid pulp is (1.1~0.8)g: (0.21~0.22)g: (1.1~0.8)g. The slurry concentration after mixing the three is 2.17~2.23g / L. During degassing, the speed is 25000-30000 rpm.

6. The method for preparing a nano-friction paper-based positive electrode material having an interpenetrating network structure according to claim 1, characterized in that: In step 3, the homogenization was performed 10 to 15 times before rapid dehydration, and the dehydration time was 1.0 to 2.0 seconds; During cold pressing, absorbent felt is placed on the upper and lower sides of the dehydrated sample. The cold pressing pressure is 20-40MPa and the time is 8-10min. During vacuum drying, the temperature is 90-100°C; the vacuum degree is 99.5-99.9 kPa; and the time is 8-10 minutes.

7. The method for preparing a nano-friction paper-based positive electrode material having an interpenetrating network structure according to claim 1, characterized in that: In step 4, during the impregnation, the average molecular weight of the carboxymethyl cellulose is 6000 to 17000, the mass fraction of the carboxymethyl cellulose solution is 0.8 wt% to 1.0 wt%, and the impregnation time is 1 to 2 min.

8. The method for preparing a nano-friction paper-based positive electrode material having an interpenetrating network structure according to claim 1, characterized in that: In step 5, during vacuum drying, the temperature is 90-100° C., the vacuum degree is 99.5-99.9 kPa, and the time is 8-10 min; During hot pressing finishing, the temperature is 180-200°C, the time is 10-20 minutes, and the pressure is 13-15 MPa.

9. A paper-based positive electrode material obtained by the method for preparing a nano-friction paper-based positive electrode material with an interpenetrating network structure according to any one of claims 1 to 8.

10. A nano friction generator, characterized in that: It comprises a positive electrode made of the positive electrode material according to claim 9 and a negative electrode made of a polytetrafluoroethylene film.

Citation Information

Patent Citations

  • A high-temperature resistant flexible triboelectric nanogenerator sensor, its fabrication method and application

    CN114938156A

  • Method for producing aramid fiber pulp by aramid fiber waste material

    CN101250771A

  • Para-aramid pulp including meta-aramid fibrids and processes of making same

    CN101341289A

  • High-air-permeability pitch-based carbon fiber base paper and preparation process thereof

    CN119162862A

  • Method for manufacturing water-resistant paper, and water-resistant paper

    JP2022064790A

Cited By

  • Self-sensing carbon fiber composite material, nanogenerator and preparation method thereof

    CN122533447A